Base-free hydrogen generation from formaldehyde and water catalyzed by copper nanoparticles embedded on carbon sheets. Issue 3 (22nd January 2019) - Chen, Xiao; Zhang, Huan; Xia, Zhaoming; Zhang, Sai; Ma, Yuanyuan
Abstract : Base-free hydrogen generation through complete dehydrogenation from formaldehyde and water catalyzed by Cu nanoparticles embedded on carbon sheets. Abstract : Catalytic dehydrogenation from formaldehyde and water provides a promising pathway to produce renewable and clean energy hydrogen resources. Copper-based heterogeneous catalysts show promise to catalytically generate hydrogen from formaldehyde. However, these catalysts incompletely dehydrogenate formaldehyde into formic acid and hydrogen in the presence of a base, leading to only partial utilization of the carrier. Herein, we report a simple and facile synthesis of uniform Cu nanoparticles embedded on carbon sheets (Cu@CS), which enable hydrogen generation through complete dehydrogenation between formaldehyde and water in the absence of any additives under mild reaction conditions. The exceptional performance is linked to the unique embedded structure of the catalysts by confining Cu nanoparticles within carbon sheets as well as the strong interaction between Cu and the supports.